2020
DOI: 10.21147/j.issn.1000-9604.2020.04.08
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of cancer susceptibility genes mutations in 282 patients with gastric adenocarcinoma

Abstract: Objective To reveal the distribution signature of cancer susceptibility genes in patients with gastric adenocarcinoma, offering a diagnostic and prognostic surrogate for disease risk management and therapeutic decisions. Methods A total of 282 patients with gastric adenocarcinoma (182 males and 100 females) were enrolled in this study, with peripheral blood genomic DNA extracted. Mutations of 69 canonical cancer susceptibility genes or presumably tumor-related genes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…However, we found a statistically significant difference between the detection of PVs in IGCs versus DGCs, suggesting that the MGPT approach may be more advantageous in selected IGCs than in selected DGCs. Interestingly, by comparison with the literature, we also observed a difference between the detection of CDH1 PVs by SGT in our selected GC patients and by MGPT in previously reported unselected patients [23,26]. Therefore, CDH1 genetic testing should preferably be recommended according to specific selection criteria.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…However, we found a statistically significant difference between the detection of PVs in IGCs versus DGCs, suggesting that the MGPT approach may be more advantageous in selected IGCs than in selected DGCs. Interestingly, by comparison with the literature, we also observed a difference between the detection of CDH1 PVs by SGT in our selected GC patients and by MGPT in previously reported unselected patients [23,26]. Therefore, CDH1 genetic testing should preferably be recommended according to specific selection criteria.…”
Section: Discussionsupporting
confidence: 65%
“…The MGPT evidenced, in addition to the PVs previously identified by SGT, two further PVs in the ATM and RAD51D genes. Contrary to ATM, previously reported as a possible candidate gene for both HDGC and FIGC, RAD51D was detected in only a few cases of GC patients [23]. Interestingly, the ATM PV carrier presented personal and family history strongly consistent with the typical clinical picture associated with this gene, being the patient diagnosed with pancreatic cancer in addition to gastric cancer and having a daughter with early-onset breast cancer.…”
Section: Discussionmentioning
confidence: 62%
“…There is a growing body of literature demonstrating that variants found on tumor DNA sequencing tests for certain high-and moderate-risk hereditary cancer risk genes are also frequently present in the germline. This has been demonstrated in paired germline-tumor tumor DNA analysis from large unselected groups of patients with diverse cancers [3,4] as well as work focused on specific cancer types [10][11][12][13][14]. Both approaches have demonstrated that tumor variants in certain hereditary cancer genes are likely to be present in the germline across a large spectrum of tumor types.…”
Section: Discussionmentioning
confidence: 96%
“…Apparently, there is no correlation between the presence of ATM PVs and the onset of a specific gastric cancer histotype as the association with ATM PVs has been described for both diffuseand intestinal-type gastric adenocarcinoma [10]. Recently, in a cohort of 282 Chinese patients with gastric adenocarcinoma tested for germline variants in a panel of 69 cancer susceptibility genes, ATM PVs were the most common, with a prevalence of 1.1% in affected individuals [20]. All identified ATM PVs were truncating (nonsense or frameshift variants) and were associated with a lower age of onset (mean age of 49.3) compared to the age of all other patients with pathogenic variants in other genes (mean age of 58.5) or to patients with no PVs from the same cohort (mean age of 60.5) [20].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in a cohort of 282 Chinese patients with gastric adenocarcinoma tested for germline variants in a panel of 69 cancer susceptibility genes, ATM PVs were the most common, with a prevalence of 1.1% in affected individuals [20]. All identified ATM PVs were truncating (nonsense or frameshift variants) and were associated with a lower age of onset (mean age of 49.3) compared to the age of all other patients with pathogenic variants in other genes (mean age of 58.5) or to patients with no PVs from the same cohort (mean age of 60.5) [20]. In comparison, the worldwide median age of onset for gastric cancer is approximately 70 years of age [21].…”
Section: Discussionmentioning
confidence: 99%